2019
DOI: 10.7189/jogh.09.011101
|View full text |Cite
|
Sign up to set email alerts
|

Understanding client and provider perspectives of antenatal care service quality: a qualitative multi-method study from Tanzania

Abstract: Background Measures of quality of care in low-and middle-income countries (LMICs) rarely include experience of care. This gap in service quality metrics may be driven by a lack of understanding of client and provider perspectives. Understanding these perspectives is a critical first step in not only improving metrics, but also in improving service delivery. This study identifies the items antenatal care (ANC) clients and health care providers in Tanzania associate with a quality ANC service and explores the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…This study’s findings also suggest that to provide more comprehensive measures of ANC quality some items could be added to SPAs and other facility surveys, particularly items related to the experience of care. While the global community is moving towards more person-centred care, data collected through health facility assessments is generally deficient in experience of care measures 47 48. This may be due to the lack of validated instruments available for measuring the experience of maternal health care 49.…”
Section: Discussionmentioning
confidence: 99%
“…This study’s findings also suggest that to provide more comprehensive measures of ANC quality some items could be added to SPAs and other facility surveys, particularly items related to the experience of care. While the global community is moving towards more person-centred care, data collected through health facility assessments is generally deficient in experience of care measures 47 48. This may be due to the lack of validated instruments available for measuring the experience of maternal health care 49.…”
Section: Discussionmentioning
confidence: 99%
“…Method used to conduct this study was Qualitative method using exploratory approach which was done with an intention to get better understanding of factors for late initiation of antenatal care in Kahama Municipal [14]. key informants were Pregnant women and health care providers.…”
Section: A Study Designmentioning
confidence: 99%
“…Further, a positive relationship between patients and providers that is marked by good rapport, empathic communication, active listening, and confidentiality, was reported to have increased utilization of health services and improved quality of care and health outcomes in LMICs. 9 Overall, improving quality of care increases the opportunity for patients' and facility-level outcomes with a focus on maximizing the utilization of health care services.…”
Section: Introductionmentioning
confidence: 99%
“… 6 8 Researchers have cited weak health system structural factors, such as longer waiting times and commodity stock-outs, among other compounded health system challenges affecting the quality of care in LMICs. 9 In terms of maternal, neonatal, and child health care, many women in LMICs lack comprehensive quality of care throughout pregnancy and delivery. 10 In Kenya, population-based research has shown that the poorest women received fewer essential services during ANC care and were 4 times more likely to deliver without a skilled attendant compared to those women in the wealthiest quintile.…”
Section: Introductionmentioning
confidence: 99%